2023
DOI: 10.3389/fvets.2023.1169766
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivities and cross-neutralization of different envelope glycoproteins E2 antibodies against different genotypes of classical swine fever virus

Abstract: Classical swine fever (CSF) is a highly contagious swine disease caused by the classical swine fever virus (CSFV), wreaking havoc on global swine production. The virus is divided into three genotypes, each comprising 4–7 sub-genotypes. The major envelope glycoprotein E2 of CSFV plays an essential role in cell attachment, eliciting immune responses, and vaccine development. In this study, to study the cross-reaction and cross-neutralizing activities of antibodies against different genotypes (G) of E2 glycoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In protein manipulation, previous studies have indicated that plant-derived transient expression enhances high protein expression and yield, immunogenicity in animal experiments, and high binding affinity for antibody detection absent in certain conventional expression systems ( Sohn et al, 2018 ; Yamamoto et al, 2018 ; Xu et al, 2022 ). Compared to the transgenic approach for CSFV E2 protein expression using baculovirus ( Wei et al, 2021 ; Bai et al, 2022 ), mammalian cells ( Ji et al, 2018 ; Chen et al, 2023 ), or the E. coli system ( Li et al, 2012 ; Yi et al, 2022 ), the CSFV E2-expressing transgenic plant-derived system was preferable in terms of a large amount and stable expression of the target protein and inexpensiveness, as in recent studies ( Sohn et al, 2018 ; Laughlin et al, 2019 ; Park et al, 2019 , 2020 ; Xu et al, 2022 ). This approach facilitated the purification of recombinant E2 from N. benthamiana extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In protein manipulation, previous studies have indicated that plant-derived transient expression enhances high protein expression and yield, immunogenicity in animal experiments, and high binding affinity for antibody detection absent in certain conventional expression systems ( Sohn et al, 2018 ; Yamamoto et al, 2018 ; Xu et al, 2022 ). Compared to the transgenic approach for CSFV E2 protein expression using baculovirus ( Wei et al, 2021 ; Bai et al, 2022 ), mammalian cells ( Ji et al, 2018 ; Chen et al, 2023 ), or the E. coli system ( Li et al, 2012 ; Yi et al, 2022 ), the CSFV E2-expressing transgenic plant-derived system was preferable in terms of a large amount and stable expression of the target protein and inexpensiveness, as in recent studies ( Sohn et al, 2018 ; Laughlin et al, 2019 ; Park et al, 2019 , 2020 ; Xu et al, 2022 ). This approach facilitated the purification of recombinant E2 from N. benthamiana extracts.…”
Section: Discussionmentioning
confidence: 99%